2011
DOI: 10.1016/j.neuropsychologia.2011.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Cortical regions recruited for complex active-learning strategies and action planning exhibit rapid reactivation during memory retrieval

Abstract: Memory retrieval can involve activity in the same sensory cortical regions involved in perception of the original event, and this neural “reactivation” has been suggested as an important mechanism of memory retrieval. However, it is still unclear if fragments of experience other than sensory information are retained and later reactivated during retrieval. For example, learning in non-laboratory settings generally involves active exploration of memoranda, thus requiring the generation of action plans for behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 50 publications
6
31
1
Order By: Relevance
“…The results from Voss, Gonsalves, et al (2011) showed an advantage for self-directed encoding for both recognition and spatial recall. A consistent pattern of results was found in a separate follow-up experiment, showing that the benefit from self-directed encoding was still evident a week after the initial study session (Voss, Galvan, et al, 2011). …”
Section: Enhanced Memory Through Self-directed Explorationsupporting
confidence: 73%
See 2 more Smart Citations
“…The results from Voss, Gonsalves, et al (2011) showed an advantage for self-directed encoding for both recognition and spatial recall. A consistent pattern of results was found in a separate follow-up experiment, showing that the benefit from self-directed encoding was still evident a week after the initial study session (Voss, Galvan, et al, 2011). …”
Section: Enhanced Memory Through Self-directed Explorationsupporting
confidence: 73%
“…A recent set of studies (Voss, Galvan, et al, 2011; Voss, Gonsalves, et al 2011; Voss, Warren, et al, 2011) found a robust benefit for self-directed memory encoding in a spatial exploration task in which participants memorized the identity and location of icons presented in a series of 5×5 grids (see Figure 1). At any given time, a single item in the grid was visible through a “window" that moved throughout the display.…”
Section: Enhanced Memory Through Self-directed Explorationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, exerting volitional controlduring object-location learning facilitates later memory of the individual objects and the related spatial locations relative to passively viewing the objects in a predetermined sequence (Voss, Galvan, & Gonsalves, 2011; Voss, Gonsalves, Federmeier, Tranel, & Cohen, 2011; Voss, Warren, et al, 2011). Taken together, these findings suggest that methods to promote active retrieval could be used to enhance encoding of novel information.…”
Section: 1 Discussionmentioning
confidence: 99%
“…It is unclear from the current results what brain regions are involved in this binding-related facilitation by active retrieval, although our previous experiment specifically implicated anterior hippocampus (Bridge & Voss, 2014). By further refining knowledge of critical brain regions in future studies, it will be possible to determine whether facilitation by active retrieval would be appropriate for use by individuals suffering from memory impairments due to damage to regions likely involved, such as hippocampus and prefrontal cortex (which are prominently involved in the influence of active retrieval and learning on memory; (Bridge & Voss, 2014 ; Voss, Gonsalves, et al, 2011; Voss, Warren, et al, 2011)). In summary, active retrieval has a unique promotional effect on integrating new information into existing memories, over and above passively encountering familiar information.…”
Section: 1 Discussionmentioning
confidence: 99%